2014
DOI: 10.2478/s11535-014-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical adaptations of Astragalus gombiformis Pomel. under drought stress

Abstract: The present study was designed to study the effect of drought on root, stem and leaf anatomy of Astragalus gombiformis Pomel. Several root, stem and leaf anatomical parameters (cross section diameter, cortex, root cortical cells, pith, leaf lamina and mesophyll thickness) were reduced under moderate to severe water deficit (20–30 days of withheld irrigation). The stele/cross section root ratio increased under moderate water deficit. The root’s and stems vascular systems showed reduced xylem vessel diameter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 51 publications
4
19
0
4
Order By: Relevance
“…They found that root length and number of secondary roots decreased, while number of medullary rays and vascular region increased under water deficit conditions. Boughalleb et al (2014) found that anatomical variations such as reduced vessel size, mesophyll thickness, and cortical parenchyma development were observed in Astragalus gombiformis under water stress conditions for the maintenance of energy storage and improved resistance for survival of the plants in dry areas. Vasellati et al (2001) reported that under water deficit conditions, diameter of root and metaxylem area decreased in Paspalum dilatatum, thereby lowering the risk of embolism, increasing the water-flow resistance and number of root hairs, which could increase the water uptake ability in the plant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They found that root length and number of secondary roots decreased, while number of medullary rays and vascular region increased under water deficit conditions. Boughalleb et al (2014) found that anatomical variations such as reduced vessel size, mesophyll thickness, and cortical parenchyma development were observed in Astragalus gombiformis under water stress conditions for the maintenance of energy storage and improved resistance for survival of the plants in dry areas. Vasellati et al (2001) reported that under water deficit conditions, diameter of root and metaxylem area decreased in Paspalum dilatatum, thereby lowering the risk of embolism, increasing the water-flow resistance and number of root hairs, which could increase the water uptake ability in the plant.…”
Section: Discussionmentioning
confidence: 96%
“…ecotypes. It is believed that anatomical modifications such as reduced vessel size, mesophyll, and cortical parenchyma formation are essential to survive under water deficit conditions (Boughalleb et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the lower epidermal cell length were seen in Astragalus gombiformis Pomel. under moderate drought stress (20 days) and severe drought stress (30 days) (Boughalleb et al, 2014). The decreasing of the size of leaf epidermal exposed to drought stress was an effect of decreasing water availability in the growing media so that the water needed for full cell turgor was not available.…”
Section: Resultsmentioning
confidence: 99%
“…The mesophyll thickness of Astragalus gombiformis Pomel. decreased significantly when exposed to moderate and severe drought stress ( 20-30 days) (Boughalleb et al, 2014). This is a leaf mechanism allowing CO2 to enter the chloroplast in the palisade tissue at the time of the opening of the reduced stomata and a plant strategy to protect photosynthesis when the plant is exposed by drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly due to the fact that the root cortex hinders water transport via the roots. Therefore, the thicker the root cortex, the greater the resistance to water transport and the smaller the rate of water absorption (Wang et al, 2005;Boughalleb et al, 2014;Enstone et al, 2002;Miyamoto et al, 2001). However, the root diameter, stele diameter, and thickness of the outer root layer under high temperature and waterlogging stress showed no significant differences with those of the CK, which was attributed to different rhizosphere temperatures.…”
Section: Discussionmentioning
confidence: 99%